Kontribusi perputaran kas dan perputaran piutang terhadap profitabilitas pada PD. BPR Kota Sukabumi periode tahun 2011 – 2017 - Deri Firmansyah; Asep Suryana; Dwinanto Priyo Susetyo; Ratna Mandasari (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to determine the contribution of the influence of Cash Turnover and Accounts Receivable Turnover to profitability either partially or simultaneously in PD. Bank Perkreditan (BPR) Sukabumi City. Research methodology: The data sample used financial reports for 7 years from 2011 - 2017 or n = 28 quarterly report data using a purposive sampling technique. Statistical analysis using t-test and F-test using the EViews 10.0 program. Results: It is found that cash-turnover and accounts receivable turnover positively and significantly impact profitability. This means that together with the independent variables (cash-turnover and accounts receivable turnover affect the dependent variable (profitability). Limitations: The limitation and focus of research studies are limited to analyzing the contribution of cash turnover and accounts receivable turnover followed by its implications for ROA. Contribution: This study's results can be taken into consideration in banking financial reports to pay more attention to cash turnover and accounts receivable turnover in an effort to increase bank profitability. Keywords: Cash turnover, Receivable turnover, Return on Assets How to cite: Firmansyah, D., Suryana, A., Susetyo, D. P., & Mandasari, R. (2021). Kontribusi perputaran kas dan perputaran piutang terhadap profitabilitas pada PD. BPR Kota Sukabumi periode tahun 2011 – 2017. Jurnal Akuntansi, Keuangan, Dan Manajemen, 2(2), 151-163.